Needs for International Benchmarking of Road Safety Management Based on Mobility Exposure Measures and Risk Patterns - González-Sánchez, Guadalupe; Olmo-Sánchez, María Isabel; Maeso-González, Elvira; Gutiérrez-Bedmar, Mario; García-Rodríguez, Antonio (MDPI, 2021)
Each year, 1.35 million people worldwide die due to Road Traffic Injuries (RTI), highlighting the need for further research. The risk of RTI is usually estimated as the number of casualties divided by the level of exposure in a population. Identifying the most appropriate exposure measures is one of the most important current challenges in this field. This paper presents an analysis of exposure measures used in empirical studies on road accidents. The results show a large variability in the exposure measures used, ranging from more general measures (such as population figures or vehicle fleet) to more specific measures related to mobility (such as number of trips, distances or travel time). A comparison of the risk patterns found shows that there is a partial consensus on the profiles with the highest risk of road traffic injuries. In conclusion, there is a need for the international standardization of criteria and data to be recorded, at least injury severity and measures of exposure to mobility, as the travel time disaggregated by socio-demographic variables and mode of transport. Such data would provide higher-quality results on risk profiles and facilitate the implementation of more effective, knowledge-based road safety policies.
Keywords: Accidentes de tráfico; Road traffic injury; Mode of transport; Injury severity; Gender; Exposure measure